Learning in a living lab : knowing what to do when you don't know what to do - Van den Hee, Mirthe, ....-; Desomviele, Lieven, ....-; Woolfitt, Zac, ....- (Gent : Owl Press, 2024)
Society faces a number of problems with so many interdependent factors that they seem impossible to solve. To find solutions for these wicked problems the world needs the collaboration of creative problem solvers from different disciplines, people who ‘know what to do when they don’t know what to do’. Higher education has created an environment where these problem solvers come together: a living lab. Lab education takes place in a real-life context, where a number of problem solvers from various backgrounds research, develop, learn and innovate in collaboration with end-users of participants. Creativity, future skills, research, interdisciplinary learning, leadership, self-management, working and learning in team, assessment… All this and more is explored in this book, so that anyone can learn about ‘learning in a living lab’. Are you ready to step into this world where there are countless options? Come with us to learn about the transformative power of Living Labs, which are places where imagination and reality meet and where new ideas come to life. Welcome to the future!
Keywords: Onderzoek en ontwikkeling